Functional Independence Through Compensatory Neurorehabilitation in a Young Adult After Severe Intracerebral Hemorrhage: A Case Report - Ani Purwati Paligar; Farida Arisanti; Dian Marta Sari (Jurnal KESANS : Kesehatan dan Sains, 2026)
Introduction: Intracerebral hemorrhage (ICH) in young adults is associated with high morbidity, particularly involves extensive lobar areas and necessitates surgical intervention. Although increased neuroplasticity is associated with younger age, the functional recovery following craniotomy can differ significantly even neuroplasticity increased in young adults. Limited evidence available on rehabilitation-focused outcomes in this population. Objective: This study aimed to describe functional recovery following a structured rehabilitation program in a young adult patient after severe intracerebral hemorrhage and craniotomy Methods: A 39-year-old man had a large left frontotemporoparietal ICH with intraventricular extension had emergency craniotomy and hematoma evacuation. Two months later, severe right-sided paralysis (Brunnstrom stage 1), shoulder subluxation, poor functional speech, and total dependence on everyday activities (Barthel Index 40/100) were evident. A structured, goal-directed rehabilitation programme was implemented over four weeks, focusing on endurance training, mobility control, compensatory strategies using the unaffected limb, cognitive stimulation and caregiver education. Results: After a month of rehabilitation, the patient achieved independent bed-to-sit mobility, increased unsupported sitting tolerance from 10 to 60 minutes, partially comprehensible speech, and improved independence in basic activities of daily living using compensatory strategies. The Barthel Index improved to 65/100 with Burnnstrom increase from 2 to 3 for right extremities and Burnnstrom 2 to 5 for left extremities. Conclusion: Young adults with severe intracerebral haemorrhage (ICH) can achieve meaningful functional independence through endurance-focused and compensatory rehabilitation strategies, even neurological motor recovery is limited. Significant functional outcomes beyond motor restoration may be achieved through rehabilitation goals targeting activity and participation.